Vera. Set 6 [videorecording (DVD)] - Blethyn, Brenda, 1946-; Morrison, Jon; Doughty, Kenny, 1975-; Cleeves, Ann; Ma, Jian, 1953- (Acorn, 2016)
Includes four all-new, feature-length mysteries. From the death of a woman found on the Northumberland cliffs to the body of a fisherman pulled out of the sea, these cases prove to be some of the most difficult and emotional in Vera's career.